Mesoporous silica microsphere and preparation method thereof
By adding hydrophobic groups diamine compounds in the preparation process of mesoporous silica microspheres and combining the addition reaction of urea and formaldehyde, the problem of difficulty in preparing submicron-scale mesoporous silica microspheres in the prior art is solved, and the preparation effect of small particle size and low cost is achieved.
Patent Information
- Application Number
- CN202411854756.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art is difficult to prepare submicron-scale mesoporous silica microspheres, and traditional methods require expensive surfactants and are costly.
By mixing urea, diamine compounds and formaldehyde, an intermediate mixed solution containing the addition product was formed, and mixed with an acidic silica sol, and allowed to stand to precipitate to obtain organic and inorganic composite microspheres, followed by calcination to obtain mesoporous silica microspheres. This method reduces the solubility of the prepolymer by introducing hydrophobic groups, improves the nucleation rate and reduces the particle size of the microspheres.
Mesoporous silica microspheres with particle sizes of 0.1 to 2 microns can be prepared, and can even reach the submicron level, with low cost and relatively simple operation.
Smart Images

Figure CN119873840A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of material technology, and in particular to mesoporous silica microspheres and a preparation method thereof. Background Art
[0002] Mesoporous silica materials have narrow nanoscale pores and huge specific surface area. As a non-metallic material, silica has good heat and moisture resistance, low thermal expansion coefficient, high strength, and good stability, which makes it have good application prospects in molecular catalysis, pharmaceutical separation, electronic packaging and other fields.
[0003] The common preparation methods of mesoporous silica microspheres include sol-gel method, hydrothermal method, polymerization-induced colloidal aggregation method, etc. Among them, sol-gel method and hydrothermal method require expensive surfactants as templates to form pores, which are costly. The polymerization-induced colloidal aggregation method uses cheap urea, formaldehyde and silica sol as raw materials. Formaldehyde and urea are added to the acidic silica sol to polymerize to form prepolymers. The prepolymers adsorb colloidal particles through hydrogen bonding. At the same time, the prepolymers further grow and polymerize. When the critical chain length is reached, they precipitate from the solution to form organic-inorganic composite microspheres. The polymers are then removed by calcination to obtain mesoporous silica microspheres. Compared with other methods, the polymerization-induced colloidal aggregation method can effectively control the particle size, pore size and distribution of organic-inorganic composite microspheres, and the cost is lower. However, the particle size of mesoporous silica prepared by the polymerization-induced colloidal aggregation method is currently in the micron level, and it is difficult to prepare mesoporous silica microspheres with smaller particle sizes (such as submicron level). Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, one object of the present invention is to provide a method for preparing mesoporous silica microspheres, which can effectively prepare mesoporous silica microspheres with smaller particle sizes.
[0005] In one aspect of the present invention, the present invention provides a method for preparing mesoporous silica microspheres. According to an embodiment of the present invention, the method for preparing mesoporous silica microspheres comprises: adding urea, a diamine compound and formaldehyde to water for mixing to obtain a mixed solution, wherein the diamine compound comprises a hydrophobic group; heating the mixed solution to a predetermined temperature, and the urea and the diamine compound react with the formaldehyde to obtain an intermediate mixed solution containing an addition product; stirring and mixing the intermediate mixed solution with an acidic silica sol, and allowing to settle to obtain an organic-inorganic composite microsphere; calcining the organic-inorganic composite microsphere to obtain the mesoporous silica microsphere. Thus, by adding a diamine compound with a hydrophobic group, the diamine compound can participate in the addition and condensation reaction with formaldehyde together with urea to generate a prepolymer of urea-formaldehyde resin. In this way, the introduction of a hydrophobic group into the prepolymer of urea-formaldehyde resin can reduce the solubility of the prepolymer in aqueous solution, increase the supersaturation of the prepolymer, and then increase the nucleation rate, thereby reducing the particle size of the organic-inorganic composite microspheres, so that after calcination treatment, mesoporous silica microspheres with a smaller particle size can be obtained. Further, the above preparation method is easy to implement and has low cost.
[0006] According to an embodiment of the present invention, the molar ratio of the urea, the diamine compound and the formaldehyde is (0.5-1): (0.001-0.5): (0.5-3.0); and / or the diamine compound includes at least one of ethylenediamine, propylenediamine, hexamethylenediamine, triethylenetetramine, and phenylenediamine.
[0007] According to an embodiment of the present invention, the molar ratio of the diamine compound to the formaldehyde is 1:(1-2).
[0008] According to an embodiment of the present invention, before the mixed solution is heated to the predetermined temperature, the pH of the mixed solution is adjusted to be alkaline in advance, and the predetermined temperature is 60°C to 85°C.
[0009] According to an embodiment of the present invention, the acidic silica sol satisfies at least one of the following conditions: the solid content of the acidic silica sol is 2%-15%; the pH of the acidic silica sol is 1-4; the molar ratio of silicon dioxide in the acidic silica sol to the formaldehyde is 1:(0.2-3).
[0010] According to an embodiment of the present invention, the stirring rate of the intermediate mixed liquid and the acidic silica sol is 200 rpm-500 rpm.
[0011] According to an embodiment of the present invention, before the calcination treatment, the organic-inorganic composite microspheres are dried in advance, and the drying temperature is 40° C.-80° C. and the drying time is 6 h-12 h.
[0012] According to an embodiment of the present invention, the conditions of the calcination treatment satisfy at least one of the following conditions: the temperature of the calcination treatment is 500°C-800°C; the rate of heating to the temperature of the calcination treatment is 10°C / min-120°C / min; the time of the calcination treatment is 2h-6h.
[0013] In another aspect of the present invention, the present invention provides a mesoporous silica microsphere. According to an embodiment of the present invention, the mesoporous silica microsphere is prepared by the method described above, thereby preparing mesoporous silica microspheres with a smaller particle size.
[0014] According to an embodiment of the present invention, the mesoporous silica microspheres meet at least one of the following conditions: the particle size of the mesoporous silica microspheres is 0.1 to 2 microns; the specific surface area of the mesoporous silica microspheres is 350-700 m 2 / g; the pore size of the mesoporous silica microspheres is 6-9nm; the total pore volume of the mesoporous silica microspheres is 0.5-1.0cm 3 / g. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0016] Figure 1 This is a flow chart of a method for preparing mesoporous silica microspheres in one embodiment of the present invention.
[0017] Figure 2 is a pore size distribution diagram of the mesoporous silica microspheres prepared in Example 7;
[0018] Figure 3 is a scanning electron microscope image of the mesoporous silica microspheres prepared in Example 7;
[0019] Figure 4 This is a scanning electron microscope image of the mesoporous silica microspheres prepared in Comparative Example 1. DETAILED DESCRIPTION
[0020] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0021] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0022] In one aspect of the present invention, the present invention provides a method for preparing mesoporous silica microspheres. According to an embodiment of the present invention, the method for preparing mesoporous silica microspheres comprises:
[0023] S100: adding urea, a diamine compound and formaldehyde into water and mixing them to obtain a mixed solution, wherein the diamine compound includes a hydrophobic group.
[0024] According to some embodiments of the present invention, in the mixed solution, the molar ratio of urea, diamine compounds and formaldehyde is (0.5-1): (0.001-0.5): (0.5-3.0), such as 0.5:0.01:0.5, 0.5:0.05:1, 0.75:0.05:1.5, 0.75:0.1:1.5, 1:0.1:1.5, 1:0.5:2, 1:0.5:3, etc. In some specific embodiments, the molar ratio of diamine compounds to formaldehyde is 1: (1-2), such as 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, etc. In this way, the addition reaction of urea, diamine compounds and formaldehyde can be effectively guaranteed, and it is helpful to improve the nucleation efficiency of microspheres; in the mixed solution, if the formaldehyde content is too low, the nucleation amount in the system will be relatively reduced, which will reduce the yield of mesoporous silica microspheres; if the formaldehyde content is too high, the polymerization rate in the system will be too fast, the ball formation will be difficult to control, and it will be easy to agglomerate to obtain irregular microsphere particles, which will relatively reduce the quality of the microspheres.
[0025] According to some embodiments of the present invention, the diamine compound includes at least one of ethylenediamine, propylenediamine, hexamethylenediamine, triethylenetetramine, and phenylenediamine. The above diamine compounds are easy to react with formaldehyde, have certain hydrophobic groups, and have a wide range of material sources and low cost.
[0026] The formaldehyde may be added in the form of a formaldehyde solution and mixed with water.
[0027] S200: The mixed solution is heated to a predetermined temperature, and urea and diamine compounds undergo addition reactions with formaldehyde, respectively, to obtain an intermediate mixed solution containing addition products. In this process, a portion of formaldehyde undergoes addition reaction with urea, and a portion of formaldehyde undergoes addition reaction with diamine compounds, that is, the addition products include addition products of formaldehyde and urea and addition products of formaldehyde and diamine compounds.
[0028] According to some embodiments of the present invention, before the mixed solution is heated to a predetermined temperature, the pH of the mixed solution is pre-adjusted to alkaline, which can facilitate the smooth addition reaction of urea, diamine compounds and formaldehyde and avoid the continued condensation reaction of the addition product.
[0029] According to some embodiments of the present invention, the predetermined temperature is 60° C. to 85° C., for example, the predetermined temperature may be 60° C., 62° C., 65° C., 68° C., 70° C., 73° C., 75° C., 78° C., 80° C., 82° C., 85° C., etc. The above temperature is conducive to the smooth progress of the addition reaction of urea, diamine compounds and formaldehyde, and reduces the occurrence of side reactions.
[0030] S300: Stirring and mixing the intermediate mixed solution and the acidic silica sol, and allowing to settle to obtain organic-inorganic composite microspheres. After the intermediate mixed solution is mixed with the acidic silica sol, the addition product in the intermediate mixed solution undergoes a polycondensation reaction to generate a prepolymer, and the prepolymer adsorbs silicon oxide nanoparticles through hydrogen bonding. At the same time, the prepolymer further grows and polymerizes and adsorbs silicon oxide nanoparticles. When the prepolymer reaches a critical chain length (the solubility of the prepolymer of the critical chain length in water reaches saturation), it precipitates from the solution to form organic-inorganic composite microspheres. In the present invention, due to the addition of diamine compounds, that is, the hydrophobic group is introduced into the prepolymer, the hydrophobicity of the prepolymer is increased, the solubility of the prepolymer in the aqueous solution can be reduced, the supersaturation of the prepolymer is increased, and the nucleation rate is increased, and the particle size of the organic-inorganic composite microspheres is reduced. In this way, the particle size of the finally obtained mesoporous silica microspheres can be reduced, that is, the mesoporous silica microspheres with smaller particle sizes are obtained.
[0031] According to some embodiments of the present invention, the method for preparing the acidic silica sol may be: adding deionized water to a certain mass percentage of silica sol to prepare a colloidal solution of a certain concentration, and then adjusting the pH to acidic with hydrochloric acid to obtain the acidic silica sol. According to some specific embodiments of the present invention, the pH of the acidic silica sol is 1 to 4, for example, the pH may be 1, 2, 3, 4, etc. Under such acidic conditions, it is beneficial to carry out the polycondensation reaction of the addition product in the intermediate mixed solution, and it is beneficial to obtain microspheres of monodisperse particles.
[0032] According to some embodiments of the present invention, the solid content of the acidic silica sol is 2%-15%, for example, the solid content of the acidic silica sol is 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, etc., which is conducive to obtaining silica microspheres with smaller particle size.
[0033] According to some embodiments of the present invention, the molar ratio of silicon dioxide to formaldehyde in the acidic silica sol is 1:(0.2-3), such as 1:0.2, 1:0.5, 1:0.8, 1:1, 1:1.2, 1:1.5, 1:1.8, 1:2, 1:2.5, 1:3, etc. This is conducive to obtaining monodisperse microspheres.
[0034] According to some embodiments of the present invention, the stirring rate of the intermediate mixed liquid and the acidic silica sol is 200rpm-500rpm, such as 200rpm, 250rpm, 300rpm, 350rpm, 400rpm, 450rpm, 500rpm, etc. In this way, it is beneficial for the reactants to fully contact each other, and thus it is beneficial for the reaction to proceed more fully. Too slow a stirring rate is not conducive to the full mixing of the reactants, and too fast a stirring rate is likely to cause the liquid to splash.
[0035] S400: calcining the organic-inorganic composite microspheres to obtain mesoporous silica microspheres.
[0036] According to some embodiments of the present invention, after the organic-inorganic composite microspheres obtained in step S300 are separated, they are washed to neutrality, and then the organic-inorganic composite microspheres are dried at a temperature of 40°C-80°C, such as 40°C, 50°C, 60°C, 70°C, 80°C, etc., for 6h-12h. In this way, the above drying conditions can dry the organic-inorganic composite microspheres well without destroying the dispersibility of the organic-inorganic composite microspheres; if the drying temperature is relatively high, otherwise the organic-inorganic composite microspheres may be bonded together, destroying their monodispersity.
[0037] According to some embodiments of the present invention, the calcination temperature is 500°C-800°C, such as 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, etc.; the rate of heating to the calcination temperature is 10°C / min-120°C / min, such as 10°C / min, 20°C / min, 30°C / min, 40°C / min, 50°C / min, 60°C / min, 70°C / min, 80°C / min, 90°C / min, 100°C / min, 110°C / min, 120°C / min, etc.; the calcination time is 2h-6h, such as 2h, 3h, 4h, 5h, 6h, etc. Therefore, under the above calcination conditions, the polymer in the organic-inorganic composite microspheres can be effectively decomposed without breaking the microspheres, that is, good quality mesoporous silica microspheres can be obtained.
[0038] According to an embodiment of the present invention, in the above-mentioned preparation method, by adding a diamine compound with a hydrophobic group, the diamine compound can participate in the synthesis reaction with formaldehyde together with urea, and the subsequent condensation reaction to generate a prepolymer of urea-formaldehyde resin. In this way, the introduction of a hydrophobic group into the prepolymer of urea-formaldehyde resin can reduce the solubility of the prepolymer in aqueous solution, increase the supersaturation of the prepolymer, and then increase the nucleation rate, thereby reducing the particle size of the organic-inorganic composite microspheres, so that after calcination treatment, mesoporous silica microspheres with a smaller particle size can be obtained. Further, the above-mentioned preparation method is easy to implement and has low cost.
[0039] According to some embodiments of the present invention, mesoporous silica microspheres with a particle size of 0.1 to 2 microns can be obtained by the above preparation method. In some specific embodiments, mesoporous silica microspheres with a particle size of submicron level can also be obtained by the above preparation method, that is, the particle size is between 0.1 micron and 1 micron, for example, mesoporous silica with a particle size of 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm, 950nm, 1000nm, etc. can be obtained.
[0040] In another aspect of the present invention, the present invention provides a mesoporous silica microsphere. According to an embodiment of the present invention, the mesoporous silica microsphere is prepared by the method described above, thereby preparing mesoporous silica microspheres with a smaller particle size.
[0041] According to some embodiments of the present invention, the particle size of the mesoporous silica microspheres is 0.1 to 2 microns. In some specific embodiments, the mesoporous silica microspheres are submicron-sized mesoporous silica microspheres with a particle size of 0.1 to 1 micron, such as a particle size of 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm, 950nm, 1000nm.
[0042] According to some embodiments of the present invention, the specific surface area of the mesoporous silica microspheres is 350 m 2 / g-700m 2 / g, for example, 350m 2 / g, 400m 2 / g, 450m 2 / g、500m 2 / g, 550m 2 / g、600m2 / g, 650m 2 / g、700m 2 / g, etc., which shows that the mesoporous silica of the present invention has a larger specific surface area.
[0043] According to some embodiments of the present invention, the pore size of the mesoporous silica microspheres is 6-9 nm, such as 6 nm, 7 nm, 7.2 nm, 7.5 nm, 7.8 nm, 8 nm, 9 nm, etc.
[0044] According to some embodiments of the present invention, the total pore volume of the mesoporous silica microspheres is 0.5 cm 3 / g-1.0cm 3 / g, for example, 0.5cm 3 / g, 0.6cm 3 / g, 0.7cm 3 / g, 0.8cm 3 / g, 0.9cm 3 / g, 1.0cm 3 / g, etc.
[0045] Example
[0046] Example 1
[0047] Weigh 2.7 g of urea, 0.3 g of ethylenediamine and 6.08 g of formaldehyde, add them into 10 g of deionized water, stir evenly, and obtain a mixed solution;
[0048] The pH of the mixed solution was adjusted to 8-9 with 5% ammonia water, and then the temperature was raised to 75°C and kept for 30 minutes to allow an addition reaction to occur, thereby obtaining a clear and transparent intermediate mixed solution containing an addition product;
[0049] Weigh 20 g of silica sol with a solid content of 30% (average particle size of 12 nm) and add it to 80 g of deionized water and start mechanical stirring at a stirring speed of 300 rpm. After stirring evenly, adjust the pH to 2 with concentrated hydrochloric acid to obtain acidic silica sol;
[0050] Then the intermediate mixed solution was quickly poured into the acidic silica sol, and the stirring was continued for 5 minutes to make it fully mixed and then the stirring was stopped. The solution was allowed to stand until it became turbid and white organic-inorganic composite microspheres were formed. The organic-inorganic composite microspheres were separated by centrifugation and washed with deionized water until neutral, and placed in a vacuum drying oven at 60°C for 6 hours to obtain dry organic-inorganic composite microspheres.
[0051] Finally, the organic-inorganic composite microspheres were placed in a muffle furnace, and the temperature of the muffle furnace was raised to 650°C at a rate of 60°C / h and kept for 4 hours. After cooling to room temperature, the mesoporous silica microspheres were taken out and the particle size of the microspheres ranged from 700 to 800 nm.
[0052] Example 2
[0053] Weigh 2.7 g of urea, 0.37 g of 1,3-propylenediamine and 6.08 g of formaldehyde, add them into 10 g of deionized water, stir evenly, and obtain a mixed solution;
[0054] The pH of the mixed solution was adjusted to 8-9 with 5% ammonia water, and then the temperature was raised to 75°C and kept for 30 minutes to allow the addition reaction to occur, thereby obtaining a clear and transparent intermediate mixed solution containing the addition product;
[0055] Weigh 20 g of silica sol with a solid content of 30% (average particle size of 12 nm) and add it to 80 g of deionized water and start mechanical stirring at a stirring speed of 300 rpm. After stirring evenly, adjust the pH to 2 with concentrated hydrochloric acid to obtain acidic silica sol;
[0056] Then the intermediate mixed solution was quickly poured into the acidic silica sol, and the stirring was continued for 5 minutes to make it fully mixed and then the stirring was stopped. The solution was allowed to stand until it became turbid and white organic-inorganic composite microspheres were formed. The organic-inorganic composite microspheres were separated by centrifugation and washed with deionized water until neutral, and placed in a vacuum drying oven at 60°C for 6 hours to obtain dry organic-inorganic composite microspheres.
[0057] Finally, the organic-inorganic composite microspheres were placed in a muffle furnace, and the temperature of the muffle furnace was raised to 650°C at a rate of 60°C / h and kept for 4 hours. After cooling to room temperature, the mesoporous silica microspheres were taken out and the particle size of the microspheres ranged from 700 to 800 nm.
[0058] Example 3
[0059] Weigh 2.7 g of urea, 0.58 g of 1,6-hexanediamine and 6.08 g of formaldehyde, add them into 10 g of deionized water, stir evenly, and obtain a mixed solution;
[0060] The pH of the mixed solution was adjusted to 8-9 with 5% ammonia water, and then the temperature was raised to 75°C and kept for 30 minutes to allow the addition reaction to occur, thereby obtaining a clear and transparent intermediate mixed solution containing the addition product;
[0061] Weigh 20 g of silica sol with a solid content of 30% (average particle size of 12 nm) and add it to 80 g of deionized water and start mechanical stirring at a stirring speed of 300 rpm. After stirring evenly, adjust the pH to 2 with concentrated hydrochloric acid to obtain acidic silica sol;
[0062] Then the intermediate mixed solution was quickly poured into the acidic silica sol, and the stirring was continued for 5 minutes to make it fully mixed and then the stirring was stopped. The solution was allowed to stand until it became turbid and white organic-inorganic composite microspheres were formed. The organic-inorganic composite microspheres were separated by centrifugation and washed with deionized water until neutral, and placed in a vacuum drying oven at 60°C for 6 hours to obtain dry organic-inorganic composite microspheres.
[0063] Finally, the organic-inorganic composite microspheres were placed in a muffle furnace, and the temperature of the muffle furnace was raised to 650°C at a rate of 60°C / h and kept for 4 hours. After cooling to room temperature, the mesoporous silica microspheres were taken out and the particle size of the microspheres ranged from 600-900nm.
[0064] Example 4
[0065] Weigh 2.7 g of urea, 0.56 g of triethylenediamine and 6.08 g of formaldehyde, add them into 10 g of deionized water, stir evenly, and obtain a mixed solution;
[0066] The pH of the mixed solution was adjusted to 8-9 with 5% ammonia water, and then the temperature was raised to 75°C and kept for 30 minutes to allow the addition reaction to occur, thereby obtaining a clear and transparent intermediate mixed solution containing the addition product;
[0067] Weigh 20 g of silica sol with a solid content of 30% (average particle size of 12 nm) and add it to 80 g of deionized water and start mechanical stirring at a stirring speed of 300 rpm. After stirring evenly, adjust the pH to 2 with concentrated hydrochloric acid to obtain acidic silica sol;
[0068] Then the intermediate mixed liquid was quickly poured into the acidic silica sol, and the stirring was continued for 5 minutes to make it fully mixed and then the stirring was stopped. The solution was allowed to stand until it became turbid and white organic-inorganic composite microspheres were generated. The organic-inorganic composite microspheres were separated by centrifugation and washed with deionized water until neutral, and placed in a vacuum drying oven at 60°C for 6 hours to obtain dry organic-inorganic composite microspheres.
[0069] Finally, the organic-inorganic composite microspheres were placed in a muffle furnace, and the temperature of the muffle furnace was raised to 650°C at a rate of 60°C / h and kept for 4 hours. After cooling to room temperature, the mesoporous silica microspheres were taken out and the particle size of the microspheres ranged from 600-800nm.
[0070] Example 5
[0071] Weigh 2.7 g of urea, 0.54 g of p-phenylenediamine and 6.08 g of formaldehyde, add them into 10 g of deionized water, stir evenly, and obtain a mixed solution;
[0072] The pH of the mixed solution was adjusted to 8-9 with 5% ammonia water, and then the temperature was raised to 75°C and kept for 30 minutes to allow the addition reaction to occur, thereby obtaining a clear and transparent intermediate mixed solution containing the addition product;
[0073] Weigh 20 g of silica sol with a solid content of 30% (average particle size of 12 nm) and add it to 80 g of deionized water and start mechanical stirring at a stirring speed of 300 rpm. After stirring evenly, adjust the pH to 2 with concentrated hydrochloric acid to obtain acidic silica sol;
[0074] Then the intermediate mixed solution was quickly poured into the acidic silica sol, and the stirring was continued for 5 minutes to make it fully mixed and then the stirring was stopped. The solution was allowed to stand until it became turbid and white organic-inorganic composite microspheres were formed. The organic-inorganic composite microspheres were separated by centrifugation and washed with deionized water until neutral, and placed in a vacuum drying oven at 60°C for 6 hours to obtain dry organic-inorganic composite microspheres.
[0075] Finally, the organic-inorganic composite microspheres were placed in a muffle furnace, and the temperature of the muffle furnace was raised to 650°C at a rate of 60°C / h and kept for 4 hours. After cooling to room temperature, the mesoporous silica microspheres were taken out and the particle size of the microspheres ranged from 800 to 900 nm.
[0076] Example 6
[0077] Weigh 2.85 g of urea, 0.15 g of ethylenediamine and 6.08 g of formaldehyde, add them into 10 g of deionized water, stir evenly, and obtain a mixed solution;
[0078] The pH value of the mixed solution was adjusted to 8-9 with 5% ammonia water, and then the temperature was raised to 75°C and kept for 30 minutes to allow the addition reaction to occur, and a clear and transparent intermediate mixed solution containing the addition product was obtained;
[0079] Weigh 20 g of silica sol with a solid content of 30% (average particle size of 12 nm) and add it to 80 g of deionized water and start mechanical stirring at a stirring speed of 300 rpm. After stirring evenly, adjust the pH to 2 with concentrated hydrochloric acid to obtain acidic silica sol;
[0080] Then the intermediate mixed solution was quickly poured into the acidic silica sol, and the stirring was continued for 5 minutes to make it fully mixed and then the stirring was stopped. The solution was allowed to stand until it became turbid and white organic-inorganic composite microspheres were formed. The organic-inorganic composite microspheres were separated by centrifugation and washed with deionized water until neutral, and placed in a vacuum drying oven at 60°C for 6 hours to obtain dry organic-inorganic composite microspheres.
[0081] Finally, the organic-inorganic composite microspheres were placed in a muffle furnace, and the temperature of the muffle furnace was raised to 650°C at a rate of 60°C / h and kept for 4 hours. After cooling to room temperature, the mesoporous silica microspheres were taken out and the particle size of the microspheres ranged from 1 to 2 μm.
[0082] Example 7
[0083] Weigh 2.4 g of urea, 0.6 g of ethylenediamine and 6.08 g of formaldehyde, add them into 10 g of deionized water, stir evenly, and obtain a mixed solution;
[0084] The pH of the mixed solution was adjusted to 8-9 with 5% ammonia water, and then the temperature was raised to 75°C and kept for 30 minutes to allow the addition reaction to occur, thereby obtaining a clear and transparent intermediate mixed solution containing the addition product;
[0085] Weigh 20 g of silica sol with a solid content of 30% (average particle size of 12 nm) and add it to 80 g of deionized water and start mechanical stirring at a stirring speed of 300 rpm. After stirring evenly, adjust the pH to 2 with concentrated hydrochloric acid to obtain acidic silica sol;
[0086] Then the intermediate mixed liquid was quickly poured into the acidic silica sol, and the stirring was continued for 5 minutes to make it fully mixed and then the stirring was stopped. The solution was allowed to stand until it became turbid and white organic-inorganic composite microspheres were generated. The organic-inorganic composite microspheres were separated by centrifugation and washed with deionized water until neutral, and placed in a vacuum drying oven at 60°C for 6 hours to obtain dry organic-inorganic composite microspheres.
[0087] Finally, the organic-inorganic composite microspheres were placed in a muffle furnace, and the temperature of the muffle furnace was raised to 650°C at a rate of 60°C / h and kept for 4 hours. After cooling to room temperature, the mesoporous silica microspheres were taken out to obtain the particle size range of the microspheres, which was 500-700nm. The pore size distribution diagram of the mesoporous silica microspheres can be found in Figure 2 , SEM images can be found at Figure 3 .
[0088] Example 8
[0089] Weigh 2.1 g of urea, 0.9 g of ethylenediamine and 6.08 g of formaldehyde and add them to 10 g of deionized water. Stir evenly to obtain a mixed solution.
[0090] The pH of the mixed solution was adjusted to 8-9 with 5% ammonia water, and then the temperature was raised to 75°C and kept for 30 minutes to allow the addition reaction to occur, thereby obtaining a clear and transparent intermediate mixed solution containing the addition product;
[0091] Weigh 20 g of silica sol with a solid content of 30% (average particle size of 12 nm) and add it to 80 g of deionized water and start mechanical stirring at a stirring speed of 300 rpm. After stirring evenly, adjust the pH to 2 with concentrated hydrochloric acid to obtain acidic silica sol;
[0092] Then the intermediate mixed solution was quickly poured into the acidic silica sol, and the stirring was continued for 5 minutes to make it fully mixed and then the stirring was stopped. The solution was allowed to stand until it became turbid and white organic-inorganic composite microspheres were formed. The organic-inorganic composite microspheres were separated by centrifugation and washed with deionized water until neutral, and placed in a vacuum drying oven at 60°C for 6 hours to obtain dry organic-inorganic composite microspheres.
[0093] Finally, the organic-inorganic composite microspheres were placed in a muffle furnace, and the temperature of the muffle furnace was raised to 650°C at a rate of 60°C / h and kept for 4 hours. After cooling to room temperature, the mesoporous silica microspheres were taken out and the particle size of the microspheres ranged from 400 to 500 nm.
[0094] Comparative Example 1
[0095] Weigh 2.3 g of urea and 6.08 g of formaldehyde and add them to 10 g of deionized water. Stir evenly to obtain a mixed solution.
[0096] The pH of the mixed solution was adjusted to 8-9 with 5% ammonia water, and then the temperature was raised to 75°C and kept for 30 minutes to allow the addition reaction to occur, thereby obtaining a clear and transparent intermediate mixed solution containing the addition product;
[0097] Weigh 20 g of silica sol with a solid content of 30% (average particle size of 12 nm) and add it to 80 g of deionized water and start mechanical stirring at a stirring speed of 300 rpm. After stirring evenly, adjust the pH to 2 with concentrated hydrochloric acid to obtain acidic silica sol;
[0098] Then the intermediate mixed solution was quickly poured into the acidic silica sol, and the stirring was continued for 5 minutes to make it fully mixed and then the stirring was stopped. The solution was allowed to stand until it became turbid and white organic-inorganic composite microspheres were formed. The organic-inorganic composite microspheres were separated by centrifugation and washed with deionized water until neutral, and placed in a vacuum drying oven at 60°C for 6 hours to obtain dry organic-inorganic composite microspheres.
[0099] Finally, the organic-inorganic composite microspheres were placed in a muffle furnace, and the temperature of the muffle furnace was raised to 650°C at a rate of 60°C / h and kept for 4 hours. After cooling to room temperature, the mesoporous silica microspheres were taken out. The particle size of the microspheres ranged from 3 to 5 μm. The scanning electron microscope image of the mesoporous silica microspheres can be referred to Figure 4 .
[0100] The data of the amounts of raw materials used in the above-mentioned Examples 1 to 8 and Comparative Example 1 and the particle sizes of the obtained mesoporous silica microspheres are shown in Table 1.
[0101] Table 1
[0102]
[0103]
[0104] By comparing the data in Examples 1 to 8 with Comparative Example 1, it can be seen that in the process of preparing mesoporous silica microspheres, by adding a certain amount of diamine compounds containing hydrophobic groups, mesoporous silica microspheres with smaller particle sizes can be effectively prepared, and even mesoporous silica microspheres with submicron particle sizes can be obtained.
[0105] By comparing Examples 1, 6, 7 and 8, it can be seen that with the increase in the amount of diamine compound added, the particle size of the prepared mesoporous silica microspheres shows a decreasing trend.
[0106] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0107] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing mesoporous silica microspheres, characterized in that: include: Adding urea, a diamine compound and formaldehyde into water and mixing them to obtain a mixed solution, wherein the diamine compound includes a hydrophobic group; The mixed solution is heated to a predetermined temperature, and the urea and the diamine compound react with the formaldehyde to obtain an intermediate mixed solution containing an addition product; The intermediate mixed solution is stirred and mixed with the acidic silica sol, and allowed to stand for precipitation to obtain organic-inorganic composite microspheres; The organic-inorganic composite microspheres are calcined to obtain the mesoporous silica microspheres.
2. The method according to claim 1, characterized in that The molar ratio of the urea, the diamine compound and the formaldehyde is (0.5-1): (0.001-0.5): (0.5-3.0); And / or, the diamine compound includes at least one of ethylenediamine, propylenediamine, hexamethylenediamine, triethylenetetramine, and phenylenediamine.
3. The method according to claim 2, characterized in that The molar ratio of the diamine compound to the formaldehyde is 1:(1-2).
4. The method according to claim 1, characterized in that: Before heating the mixed solution to the predetermined temperature, adjusting the pH of the mixed solution to be alkaline; And / or, the predetermined temperature is 60°C to 85°C.
5. The method according to any one of claims 1 to 4, characterized in that: The acidic silica sol satisfies at least one of the following conditions: The solid content of the acidic silica sol is 2%-15%; The pH of the acidic silica sol is 1 to 4; The molar ratio of silicon dioxide in the acidic silica sol to the formaldehyde is 1:(0.2-3).
6. The method according to any one of claims 1 to 4, characterized in that: The stirring rate of stirring the intermediate mixed liquid and the acidic silica sol is 200 rpm-500 rpm.
7. The method according to any one of claims 1 to 4, characterized in that: Before the calcination treatment, the organic-inorganic composite microspheres are dried in advance, and the drying temperature is 40° C.-80° C. and the drying time is 6 h-12 h.
8. The method according to any one of claims 1 to 4, characterized in that: The calcination treatment conditions satisfy at least one of the following conditions: The calcination temperature is 500°C-800°C; The rate of heating to the calcination temperature is 10°C / min-120°C / min; The calcination time is 2h-6h.
9. A mesoporous silica microsphere, characterized in that: The mesoporous silica microspheres are prepared by the method according to any one of claims 1 to 8.
10. The mesoporous silica microspheres according to claim 9, characterized in that: The mesoporous silica microspheres meet at least one of the following conditions: The particle size of the mesoporous silica microspheres is 0.1 to 2 microns; The specific surface area of the mesoporous silica microspheres is 350-700 m 2 / g; The pore size of the mesoporous silica microspheres is 6-9 nm; The total pore volume of the mesoporous silica microspheres is 0.5-1.0 cm 3 / g.